Bioclimatic criteria in the AMOF building to reduce the emission of Carbon Dioxide (CO₂) -Lima -Peru 2021 - Gómez Ríos, Alejandro Enrique; Vilchez Yupanqui, Stefany Marjorie (Entrópico Arquitectura y Urbanismo, 2025)
This research aims to analyze the influence of the application of bioclimatic criteria in buildings to obtain integral well-being, energy efficiency and reduction of carbon dioxide (CO₂) to the environment. The growing trend for the use of sun-exposed glass in buildings, which causes the greenhouse effect, increases the interior temperature of the building and causes glare, promoting artificial cooling by inefficiently using energy; heating a room naturally and then cooling it artificially is a bad practice and stimulates the closing of the curtains, which causes the lighting of luminaires; with which the building emits carbon dioxide (CO₂) to the environment, contributing to global warming. It has been developed, with a methodological approach based on the principles of bioclimatic architecture, the analysis of the variables that allow to study this influence, in the office buildings in Miraflores (Lima, Peru), considering the AMOF building under adverse thermal and light conditions. With the results obtained, it is verified that the solution with solar geometry proposed for the AMOF building solves problems of thermal wellbeing, lighting and decreases the emission of carbon dioxide (CO₂) by 74.07 %. Therefore, it is concluded, that these considerations that were not regarded, influence the conditions of habitability and well-being of users, making the window the weakest point of the building to achieve human well-being, energy efficiency and reduction of pollution to the environment.